Forgotten Victims of War: A Rapid Review of Counseling Needs and a Proposed Intervention Model for Civilian Survivors - Runna Alghazo; Paola Premuda-Conti (Psychiatry International, 2024)
The counseling needs of civilian war victims, particularly those not classified as refugees, have been largely neglected in academic counseling research. This study addresses this gap by conducting a rapid literature review to evaluate the current state of counseling services available to these individuals. Using Google Scholar and Web of Science, we identified and reviewed studies on counseling services for war veterans, refugees, and civilians in conflict zones. This review revealed a significant lack of structured counseling support for non-refugee civilian war victims, despite their high vulnerability. Findings indicate that while substantial efforts have been made to support refugees and veterans, the mental health needs of civilians who remain in conflict areas are often unmet, with existing services being sparse and inadequately documented. To address this issue, we propose a preliminary model that includes culturally sensitive counseling programs, training for local counselors, and international collaboration to provide sustainable support. This study highlights the urgent need for focused research and practical interventions to develop comprehensive counseling programs for these overlooked victims of war, and encourages researchers to address this critical gap in mental health services.